UM SISTEMA DE SUPORTE A DECISÃO PARA PLANEJAMENTO DE REDES DE SENSORES SEM FIO AQUÁTICAS - Da Conceição Lima, Caroline; Sousa, Jonathan; Henrique Viana De Freitas, Francisco (LINKSCIENCEPLACE, 2026)
Wireless sensor networks are a type of ad hoc network composed by devices called sensors. Sensor networks may be used to monitor temperature, humidity, salinity, luminance, among other measures. A sensor has a sensory capacity, data processing and data communication. Sensors have a battery as an energy source. The main problem on sensor networks is to maximize the lifetime of the network. For this reason, we need to minimize the power consumption of the network ensuring an acceptable percentage of coverage of the area to be monitored, through the user-defined feature of the application. In this work, we propose to monitor the water quality in environments such as ponds and rivers. We developed a support decision system as a web application to manage data about the types of sensors on the market with its different features such as battery capacity, maximum communication radius, sensing radius as well as the model of energy consumption. This tool allows the manager to create scenarios where should contain the number of sensors of each type he has and the dimensions of the area to be monitored. We developed an integer programming mathematical model that was integrated to the web application and determines the best location for each sensor node, power consumption of each sensor at each instant, when the battery of each sensor node is over and the maximum time of life network without replacing sensor. The decision support system also presents some statistics graphically like the percentage of each pollutant in the water in order to support the manager in the task of deciding what measures should be adopted to improve the quality of water monitored by the sensor network.